ANALISIS KEPUTUSAN NASABAH DALAM PEMBIAYAAN SYARI'AH PADA PEDAGANG ANGSO DUO KOTA JAMBI - M. Nazori; Mohammad Orinaldi; Redo Saputra (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
The purpose of this study is to find out and analyze customer decisions in using Business Capital Financing for Islamic Financial institutions on Angso Duo traders in Jambi City. This research method is descriptive qualitative. The results showed that (1) the characteristics of the majority of respondents were women with a proportion of 56 percent and the remaining 44 percent were men. Then the largest proportion of respondents based on age was from respondents aged > 35 years as much as 52 percent. Furthermore, the largest proportion of respondents based on education was from respondents with high school/vocational high school education with a total of 12 people and the proportion was 48 percent of all respondents. Then the largest proportion of respondents based on income is from respondents with an income of Rp. 3,000,000 – Rp. 4,999,999 with the number of respondents as many as 10 people and the proportion of 40 percent of all respondents. Then the largest proportion of respondents based on the use of financing institutions is from respondents who use Islamic Bank financing institutions, namely with the number of respondents as many as 9 people and the proportion is 36 percent of all respondents, while the largest proportion of respondents based on the financing received is from respondents with financing received by > Rp. 5,000,000 with a total of 10 respondents and a proportion of 40 percent of all respondents, (2) Based on the results of the study it shows that cultural, social and marketing mix factors are the factors that determine the decisions of Angso Duo market traders in Jambi City in using institutional Business Capital Financing Sharia Finance.